Changes in the nasal mucosa after exposure to copper salt dust. A preliminary report. - Askergren, A.; Mellgren, M. (Scandinavian Journal of Work, Environment & Health, 1975)
Ten mental workers with varying exposure to complex copper salts to dust form, six other metal workers not exposed, and nine construction workers in other occupational categories, also unexposed to the salts, were compared with respect to history and mucosal changes in the nose. There were subjective symptoms of metal dust exposure in the group exposed to the copper salts. Suspected early atrophic changes in the mucous membranes were noted in subjects exposed for long periods of time. Protective equipment in the form of breathing masks should be used in this type of work unless moistening or a surface finish on the copper sheeting is capable of preventing the release of dust.
Keywords: copper salt dust; exposure; industrial exposure; metal work; nasal mucosa; salt dust